If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x(3x+8)=2x(7x+6)
We move all terms to the left:
5x(3x+8)-(2x(7x+6))=0
We multiply parentheses
15x^2+40x-(2x(7x+6))=0
We calculate terms in parentheses: -(2x(7x+6)), so:We get rid of parentheses
2x(7x+6)
We multiply parentheses
14x^2+12x
Back to the equation:
-(14x^2+12x)
15x^2-14x^2+40x-12x=0
We add all the numbers together, and all the variables
x^2+28x=0
a = 1; b = 28; c = 0;
Δ = b2-4ac
Δ = 282-4·1·0
Δ = 784
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{784}=28$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(28)-28}{2*1}=\frac{-56}{2} =-28 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(28)+28}{2*1}=\frac{0}{2} =0 $
| 4•b=1.6 | | 3(x-2)+10=3x+4 | | -3x+33=-12 | | 9x-17=19+9x | | 80(80-x)=90 | | a=9+3 | | -6+2w=-16 | | 0.2(4x+3)=1.4x | | 8x-1=23-4x* | | 8(5x+3x)+2=9 | | -6x+365=-40x+3x | | 75=(2x+1) | | 2/3+k=8 | | 56(x-16)=9- | | 7x−3=7(x−3) | | x^2+3x=(x+1)(x+3) | | 8=8v-4(2v+8)* | | v-20=1 | | z÷6=12 | | 2=-7w+4(w+2) | | -68-3x+5=23 | | 4(7-5)=6(4x-2) | | 10+8r=4r+20 | | 2x^2-12=108 | | 13=14a | | 4(7-5)=6(4x-2 | | 18=m-10 | | -8y+3(y-4)=18 | | 52+(3n+5)=71 | | 2/3(6x-3/2)=3-x | | -7(1-6x)-6x=6(x-7)+5 | | 6(v+6)-8v=20 |